Postać wdowy w Ewangelii Łukasza jako symbol Kościoła w tradycji łacińskiej - Bardski, Krzysztof (Vox Patrum, 2022)
The article analyzes ancient and medieval interpretations of the figure of the widow in the Gospel of Luke in the tradition of the Western Church. From Ambrose (+397), through Bede the Venerable (+735), to the compilation Glossa Ordinaria (twelfth century), the figure of the widow was mostly associated with Ecclesia, or the Church. The following research problems were addressed in the course of the deliberation: How does the biblical text suggest such an association? What potential symbol-forming motifs of the biblical text lead to this association, and what are the further implications? What was the interpretative procedure of the commentators of that time, which led to the creation of such symbolism? And finally, to what extent can it be inspiring for the modern audience? The widow Anna, who longs with hope to see God's face (Lk 2:36-38), the widow of Zarephath of Sidon, who is threatened with starvation (Lk 4:25-26), the widow of Nain, who suffers from the death of her son (Lk 7:11-17), the widow persistently begging the judge to intercede for her (Lk 18:1-8) and the widow throwing two pennies into the treasury (Lk 21:1-4) portray the Church looking with hope for the resurrection in the last times, receiving the spiritual nourishment of the Body of the Lord, trusting in the power of Christ, who restores life to her spiritually dead sons, persistently praying to God and basing her entire existence on Him.